Interpreting the maternal organisation - Höpfl, Heather; Kostera, Monika, 1963- (Routledge studies in human resource development, 2003)
This book examines the organization as embodied experience. An international range of contributors is assembled to deal explicitly with the 'maternal' aspects of organization.